Personality and interpersonal aspects of the work environment - Swiden Wick, RoseAnn (2013)
Workplace arrogance has emerged as a research focus area for many industrial-organizational psychologists. Employees who demonstrate arrogance tend to demonstrate poor job performance, executive failure and poor overall organizational success. The present study investigates arrogance measured by the Workplace Arrogance Scale (WARS: Johnson et al., 2010) in relation to the Honesty Humility facet of the HEXACO Personality Index-Revised (HEXACO PI-R: LEE & Ashton, 2004). A total of 273 participants completed the WARS and HEXACO PI-R Honesty-Humility Facet of the HEXACO. Results show significant, strong negative correlations between the Honesty-Humility subfacets and the overall Honesty Humility facet score with the WARS scores. These findings indicate that workers high in arrogance lack important honesty-humility characteristics. Once we fully understand the complex mixture of personality traits that make up workplace arrogance, we can begin to screen for it in the hiring process and develop ways to better address it in the workplace